Alejandro Parra and Dante’s Eighth Circle of Hell - Cardeña, Etzel (Journal of Scientific Exploration, 2021)
None, as it is a short commentary, but if you need one, here it is. This commentary places Alejandro Parra's very long list of plagiarisms and data missrepresentations within the context of Dante's classification of human foibles. The responses from two Argentinean universities are described, along with continuing examples of Parra's misrepresentations.